2021
DOI: 10.1007/s40261-021-01085-8
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of a COVID-19 Vaccine in a Danish Context

Abstract: Background and ObjectivesCovid-19 vaccines approved by the EU, UK and USA have been found to be safe and effective. The cost effectiveness of these vaccines depends upon a number of factors. The aim of this paper is to explore the cost effectiveness of a COVID-19 vaccine and to analyse how the price of the vaccine and the cost of administrating it influence its cost effectiveness. Methods We considered an epidemiological model developed by an expert group within 'Statens Serum Institut', which is a unit under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(80 citation statements)
references
References 9 publications
(10 reference statements)
1
77
0
Order By: Relevance
“…Our results were consistent with previous cost-effectiveness studies and can improve their findings as these studies were done at the early stage of the COVID-19 pandemic with insufficient data on the efficacy and vaccine cost. Specifically, evidence from high-income countries showed that in general vaccination was cost-saving (43)(44)(45) and cost-effective (46,47), and the whole society can benefit from vaccination even when the coverage rate was at 60% (44). As for low-and middle-income countries, vaccination was cost-saving from a societal perspective (10,48).…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with previous cost-effectiveness studies and can improve their findings as these studies were done at the early stage of the COVID-19 pandemic with insufficient data on the efficacy and vaccine cost. Specifically, evidence from high-income countries showed that in general vaccination was cost-saving (43)(44)(45) and cost-effective (46,47), and the whole society can benefit from vaccination even when the coverage rate was at 60% (44). As for low-and middle-income countries, vaccination was cost-saving from a societal perspective (10,48).…”
Section: Discussionmentioning
confidence: 99%
“…The two remaining studies were conducted in multiple countries; the first one comprised four analyses from LMICs and two analyses from HICs [ 36 ], while the other study comprised 12 analyses in LMICs [ 42 ]. Sixteen studies were conducted in 2021 [ 21 - 28 , 30 - 33 , 35 - 37 , 41 ], while nine studies were conducted in 2022 [ 29 , 34 , 38 - 40 , 42 - 45 ]. Most of the included studies (21/25) aimed to estimating the economic evaluation of different vaccination strategies [ 21 - 30 , 32 , 33 , 35 - 38 , 40 , 42 - 45 ], while two studies were conducted with the goal of estimating the economic evaluation of vaccination vs no vaccination [ 34 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies were conducted in 2021 [ 21 - 28 , 30 - 33 , 35 - 37 , 41 ], while nine studies were conducted in 2022 [ 29 , 34 , 38 - 40 , 42 - 45 ]. Most of the included studies (21/25) aimed to estimating the economic evaluation of different vaccination strategies [ 21 - 30 , 32 , 33 , 35 - 38 , 40 , 42 - 45 ], while two studies were conducted with the goal of estimating the economic evaluation of vaccination vs no vaccination [ 34 , 41 ]. Only one study assessed the economic impact of booster vaccination [ 31 ], while another compared the intradermal vaccine with the intramuscular vaccine [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A vast majority of countries have provided vaccinations to safeguard the population and economy throughout the pandemic. A regular vaccination strategy was proven to be cost-saving [ 2 , 3 , 4 ] and cost-effective [ 5 , 6 ] in both high-income countries (HICs) and in low- and middle-income countries (LMICs) [ 7 , 8 ]. However, with the variation in viruses across the globe and the waning vaccine effectiveness (VE) against viruses providing booster vaccination to fully vaccinated populations have been considered in many countries.…”
Section: Introductionmentioning
confidence: 99%